Las demandas informativas de los usuarios relacionadas con la calidad de servicios que presta la biblioteca del colegio nacional Amazonas de la ciudad Francisco de Orellana, provincia de Orellana. Periodo 2013 – 2014 - Cuenca Correa, Carmen Elena (2014)
This thesis entitled: “THE USER INFORMATION CLAIMS RELATED WITH THE SERVICES QUALITY THAT OFFER AMAZONAS COLEGIO NACIONAL LIBRARY FRANCISCO DE ORELLANA CITY, ORELLANA PROVINCE. PERIOD 2013 – 2014.” It has been structured and developed according to the regulations of graduation from the Loja National University. The general objective that guided there search was: Contributing to their search results to satisfy the informational demands of teachers and college students using library services. The methods used for the preparation of this research work were: Scientist, Analytical-Synthetic, Inductive-Deductive, and Statistical Model. Specific techniques, to which he resorted, are: Interview with the library staff to determine the informational demands of teachers and students and the quality of services provided by Colegio Nacional Amazonas, Francisco de Orellana parish; and Survey of teachers and students, to establish library services need to be improved to satisfy the information needs of users. According to the results of the interview with library staff determines that there is a clear relation between the satisfactions of timely information to teachers and student from Colegio Nacional Amazonas Library and the quality of service provided by the library claims. When the Library offers quality services that meet their users, are resolved user demands. The results of the survey applied to teachers and students of the College, determined that 91% of teachers and 81%of students surveyed indicated that meeting the demands required to improve the Electronic Reference Service(internet and /or databases);83% of teachers and 80% of students said theConsultationRoomService;78% of teachers and 71% of studentsoftheGeneralLoanCollection;77% of students and 65%oftheteachersReferral Services(guidance on searches);87% of teachers and 62%ofstudentsConsultationsjournals;28% of students and 22%ofteachersObtainingbooksviaInterlibraryLoan;and, 26%of students and17% of teachers Training Users.